(untitled) (Semiárida, 2020)
The objective of this work was to evaluate the agronomical performance of seven "Anco" pumpkin cultivars in the semiarid region of La Pampa. A comparative yield and fruit quality experiment was carried out at EEA INTA Anguil during the growing season of 2008. AII crops were planted on 25/11/08 and harvest of all materials took place on 17/03/09. Seven different cultivars were tested: Saxo (Basso), Experimental bushy material (INTA), Experimental material (INTA), Coco (Basso), Atlas (Sakata), Cuyano INTA and Waltham Butternut (Seminis). The experimental design was a randomized block with 4 replications. Each plot included 10 plants separated by 1 m and 2 m between rows. Statistical analysis using ANOVA and Scott & Knott test were performed on the data. Saxo and Atlas cultivars showed a significant total and commercial yields. In commercial yield besides the mentioned, the Material Experimental lNTA stood up. The Material Experimental lNTA showed a smaller percentage of waste, together with Cuyano INTA. Atlas showed a greater fruit size, reaching an average weight of 2.75 kg. Atlas and Waltham Butternut showed a cylindrical form of fruit, while the rest of the materials were piriform.